2020
DOI: 10.3389/fgene.2020.00469
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Encodes Small, Secreted Proteins That Contribute to Resistance to Septoria Tritici Blotch

Abstract: During plant-pathogen interactions, pathogens secrete many rapidly evolving, small secreted proteins (SSPs) that can modify plant defense and permit pathogens to colonize plant tissue. The fungal pathogen Zymoseptoria tritici is the causal agent of Septoria tritici blotch (STB), one of the most important foliar diseases of wheat, globally. Z. tritici is a strictly apoplastic pathogen that can secrete numerous proteins into the apoplast of wheat leaves to promote infection. We sought to determine if, during STB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Due to the near distance between our identified gene model and the previous findings, we can conclude that 6D chromosome seems to carry important genes which are effective against a wide range of Pt races. The second common gene model identified on 6D chromosome (TraesCS6D02G389600) was found to control the disease resistance in wheat indirectly by controlling signal peptide peptidase-like protein, one of wheat secret proteins which enable it to resist foliar disease like LR ( Zhou et al, 2020 ). It was reported that rust pathogen destroys the host cell by producing hydrolase enzyme that degrades the host plant proteins ( Pinter et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the near distance between our identified gene model and the previous findings, we can conclude that 6D chromosome seems to carry important genes which are effective against a wide range of Pt races. The second common gene model identified on 6D chromosome (TraesCS6D02G389600) was found to control the disease resistance in wheat indirectly by controlling signal peptide peptidase-like protein, one of wheat secret proteins which enable it to resist foliar disease like LR ( Zhou et al, 2020 ). It was reported that rust pathogen destroys the host cell by producing hydrolase enzyme that degrades the host plant proteins ( Pinter et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Z. tritici was cultured by inoculating potato dextrose agar (PDA) with 10 μl of the glycerol stock and incubating the Petri dishes under near-ultraviolet light for 7 days at 20 °C, 12:12 h light:dark cycle). Inoculum was prepared as described in Zhou et al , (2020) [ 50 ], ,and adjusted to a solution of 1 × 10 6 spores ml − 1 + 0.02% Tween20. (Fisher Bioreagents, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Only yeast cells co-expressing ZtSSP2 and TaE3UBQ 126–219 grew on selective medium (SD/-Leu-Trp-His) (middle panel) and showed α-galactosidase activity encoded by α-galactosidase (MEL1) (right panel). BD-TaSSP6 and AD-Zt06 were used as positive controls ( Zhou et al , 2020 ). The experiment was repeated independently three times, three plates per experiment with similar results.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of protein–protein interactions was performed using the Gal4 two-hybrid assay as described in Perochon et al (2010) . As a negative control to ensure specific interactions with ZtSSP2, another small secreted effector candidate (ΔSP) Zt-10 was used ( Kettles et al , 2017 ), while the positive control included TaSSP6 and Zt-06 ( Zhou et al , 2020 ).…”
Section: Methodsmentioning
confidence: 99%